2021
DOI: 10.1038/s41598-021-03362-0
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a core collection of native Perilla germplasm collected from South Korea based on SSR markers and morphological characteristics

Abstract: The leaves and seed oil of Perilla crop (Perilla frutescens L.) have attracted interest as health foods in East Asia. This crop has been traditionally cultivated and used for a long time as a folk plant, especially in Korea. In our study, the 22 SSR markers and eight morphological traits were used to assess the genetic diversity and population structure, to select a core collection of 400 Perilla accessions conserved in the RDA-Genebank of South Korea. A total of 173 alleles were detected and the number of all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
16
1
Order By: Relevance
“…frutescens , which is used as an oil, condiment, and vegetable (for wraps and salads) crop; and cultivated var. crispa , which is used as a Chinese herbal medicine and vegetable (for pickles and salads) crop [ 1 , 2 , 3 , 4 , 5 ]. Today, these two varieties (var.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…frutescens , which is used as an oil, condiment, and vegetable (for wraps and salads) crop; and cultivated var. crispa , which is used as a Chinese herbal medicine and vegetable (for pickles and salads) crop [ 1 , 2 , 3 , 4 , 5 ]. Today, these two varieties (var.…”
Section: Introductionmentioning
confidence: 99%
“…frutescens is extensively cultivated and used mainly in South Korea, while var. crispa is extensively cultivated and used mainly in Japan [ 1 , 2 , 3 , 5 , 6 , 7 ]. However, the origin of the Perilla crop is believed to be China, because China has a long cultivation history, high genetic diversity, and many resources distributed in the country [ 1 , 2 , 3 , 4 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reveals that the diversity in the core collection has increased. In the core collection established from the germplasm of the Perilla frutescens L. was also observed that the averages of Shannon and Nei diversity indices in the Core collection were higher than those in the total collection [99]. In can be concluded that the constructed core collection facilitates experiments to evaluate germplasm under different environmental conditions and the breeding programs in the future.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic diversity of plant genetic resources (PGRs), which provide useful alleles linked to plant development and improvement, is critical for the conservation and utilization of germplasm conserved in a gene bank [ 21 , 22 ]. DNA molecular markers provide valuable information for analyzing genetic diversity, genetic relationships, population structure, and core collections in a variety of crop species [ 23 , 24 , 25 , 26 , 27 , 28 ]. Representative core collections have been selected in various crops using different sampling strategies and clustering methods [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%